Rajah: Islamic Talisman for Overcoming Disease - Mochammad Maola; Syed Mahbubul Alam Al-Hasani (Teosofia: Indonesian Journal of Islamic Mysticism, 2023)
The coronavirus disease has been a terrible disaster around since 2019. Various fields of science have contributed to fighting the pandemic. Traditional medicine, multiple therapies, patience, and so on are kinds of contributions from Islam. Talisman or rajah is one of the Islamic traditions. There are many rajahs to prevent or fight the plague. Al-Bulqini's rajah is the focus of this research. Talisman in Islamic culture, moreover in Indonesia, will be discussed in this article. The practice of using talismans to overcome disease is a topic that has been discussed previously. Unfortunately, the practice of using amulets has become less because many Muslims tend to seek more reasonable methods to overcome and fight the disease. Whether the talisman, the Muslim who makes the talisman, or the Muslim belief in the talisman is still questionable. This research studies and elaborates on the culture of making talismans, especially to fight the plague with COVID-19 as a focus.Contribution: This study is essential in contributing to the fact that dealing with the plague can be done in various ways, including from a religious perspective, namely the use of the Rajah, which is common among Muslims. So, treatment can be made not only by a medical approach but also by a religious one.